Pressure dressings in mastoid and middle ear surgery: are they necessary? A retrospective review of patient outcomes. Issue 10 (23rd January 2018) - O'Brien, Justin Xavier; Ruskin, Olivia; Price, Tim
Abstract : Background: The application of mastoid pressure dressings following mastoid and middle ear surgery is widely practised to reduce the risk of haematoma and seroma. There are a number of minor morbidities associated with use of the dressings, as well as a financial cost associated with an overnight stay in hospital or a return appointment for removal of the dressings. The benefit of having these dressings in situ overnight is questionable. Methods: A retrospective review of 133 patients who had their mastoid dressing removed 2 h after their procedure was undertaken at our Hospital. The patient records were scanned for procedure‐related morbidities, and perioperative data were analysed. Results: No haematomas or seromas occurred in any of the 133 patients studied. Minor morbidities associated with prolonged use of mastoid pressure dressings were avoided. Conclusion: Removal of mastoid pressure dressings 2 h following ear surgery is safe and effective. Furthermore, a mastoid dressing should not be a factor in the decision as to whether to treat a patient as a day case or overnight admission.